Analysis of chemistry textbook for high school class x in firts semester of 2013 curriculum reviewed from toulmin argumentation - Made sukma erna (Universitas Pendidikan Ganesha, 2020)
This study aimed to described argumentation pattner of chemistry textbooks for high school class X in firts semester of 2013 Curriculum. This type of research is qualitative with document analysis. Research instrument is researcher himself helped with material analysis based on Toulmin's argument. Data was collected using descriptive techniques and analysis. The results of the study found that the presentation of the pattern of argumentation of textbooks in class X of SMA X 2013 Semester I was suspected of being from Toulmin included Ground-Claim (20%), Ground-Warrant-Claim pattern (4.25%), Ground-Warrant-Claim (Backing) pattern (3.40%), Ground-Warrant (Backing) pattern -Claim (Qualifer) ( 0.85%), Ground-Claim (Qualifer) (0.43%), Ground-Claim (Rebutal) pattern (0.85%), Ground-Warrant-Claim (Rebutal) (Qualifer) pattern (0.43%).